Bolted glulam beam-column connections under different combinations of shear and bending. (15th February 2019) - Wang, Mingqian; Song, Xiaobin; Gu, Xianglin; Tang, Jianyang
Highlights: Mechanical behavior of bolted glulam beam-column connections subjected to combined loading was studied. Various shear-to-bending ratios were considered in monotonic connection tests. A FEM model considering elastic-plastic damage behavior of wood and wood foundation effect was established. A quadratic/linear interaction function was proposed for the shear and moment interaction. Abstract: Bolted glulam beam-column connections are often subjected to combined shear force and bending moment induced by the semi-rigid nature of such connections. This paper summarizes the results of a series of experimental and numerical studies on the mechanical behavior of such connections under various combinations of shear force and bending moment, defined by the shear-to-moment ratio λ  . Monotonic loading tests, including pure bending tests ( λ  = 0), pure shear tests ( λ = ∞), and combined shear and bending tests ( λ  = a limited value), were conducted. A three-dimensional finite element method based model was established, validated and used for a parametric study focusing on the influence of the shear-to-bending ratio on the combined load carrying capacity of the connections. The test results indicated that perpendicular to grain tensile splitting and parallel to grain shear splitting are the two major failure modes. The moment resistance decreased with the increase of the shear-to-bending ratio by up to 31.6% of the pure moment resistance, and the shear resistance decreased with the decrease of the shear-to-bending ratio by up to 46.1% of the pure shear resistance, implying a strong interaction between the shear force and the bending moment. Eventually, a quadratic interaction function was proposed for connections with the shear-to-moment ratio less than 1.53, otherwise a linear interaction function was proposed.